Comparison of high hydrostatic pressure and thermal processing on microorganisms and quality of anthocyanin-rich fruit puree - Yang, Xuan; Ding, Haoyue; Luo, Sijia; Sun, Xiaojun; Wang, Niu; Wang, Yongtao (Frontiers in Food Science and Technology, 2022)
High hydrostatic pressure (HHP, 400 MPa/10 min and 500 MPa/8 min) and thermal processing (TP, 90°C/2 min) were comparatively evaluated by examining their impacts on microorganisms, physicochemical characteristics (TSS, pH, color, ascorbic acid, total phenols, total anthocyanins, and particle size distribution), antioxidant activity, endogenous enzyme activity, and sensory quality of the anthocyanin-rich fruit puree during 20 days of storage at 4°C. The count of total aerobic bacteria (TAB) in HHP treated samples was less than 2.02 log10CFU/mL, and yeasts and molds (Y&M) were not detected during storage. Compared with TP treated samples, the total anthocyanins, total phenols, ascorbic acid, antioxidant capacity, and color of HHP treated ones were better maintained. Principal component analysis (PCA) also proved that the original quality of puree could be better preserved by HHP after treatment and during storage. However, the activity of polyphenol oxidase (PPO) and pectin meth esterase (PME) in HHP treated samples were not inactivated totally. In sum, better quality parameters were observed in HHP treated samples, so HHP was a potential way to be applied to fruit puree.